Protocol for cell image-based spatiotemporal proteomics in budding yeast - Athanasios Litsios; Myra Paz David Masinas; Helena Friesen; Charles Boone; Brenda J. Andrews (STAR Protocols)
Summary: The eukaryotic cell division cycle is a highly conserved process, featuring fluctuations in protein localization and abundance required for key cell cycle transitions. Here, we present a protocol for the spatiotemporal analysis of the proteome during the budding yeast cell division cycle using live-cell imaging. We describe steps for strain construction, cell cultivation, microscopy, and image analysis. Variations of this protocol can be applied for the spatiotemporal analysis of the proteome in different contexts, such as genetic and environmental perturbations.For complete details on the use and execution of this protocol, please refer to Litsios et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.